(untitled) (London Journal of Medical and Health Research, 2026)
Hiatal hernias of types II-IV have anatomical features that cause a displacement of the abdominal organs into the mediastinum through the hiatal opening of the diaphragm parallel to the esophagus without or together with it (paraesophageal component), which is an absolute indication for surgical treatment, since it is the cause of life-threatening conditions (acute intestinal or gastric, esophageal obstruction, strangulation and further necrosis of the organs located in the hernial sac). The recurrence rate of hiatal hernias of types II-IV reaches 20-40% and even 60%, underscoring the need for analysis and search for new solutions to this problem. The article analyzes the long-term results of treatment of 150 patients with hiatal hernias of types II-IV hernias, operated in the thoracic surgery department of the P.A. Bayandin Murmansk Regional Clinical Hospital in the period from 2013 to 2017, which made up a retrospective group (standard surgical treatments). Based on the assessment of the treatment results, changes were made to the surgical intervention tactics used. From 2018 to 2024, 180 patients with hiatal hernias of types II-IV underwent surgery in the same unit, forming a prospective study group (optimal surgical treatments). A comparison of these groups was carried out. The research evaluates the perception of certain factors, primarily shortening of the esophagus, as objective conditions with the transformation of surgical tactics allowing for achieving significantly better results. Good or satisfactory treatment outcomes were achieved in 73.7% of cases in patients of the retrospective group, and poor outcomes were achieved in 26.7%. In patients of the prospective group, these results were 88.6% and 11.4%, respectively. The research confirms that with shortening of the esophagus in type III hernias, its high mobilization does not allow to reliably prevent repeated displacement of the stomach into the chest; the use of prostheses to correct the esophageal hiatus in case of shortening of the esophagus is an ineffective method of preventing relapse of the disease; the formation of a fundoplication cuff in the mediastinum in case of shortening of the esophagus should be considered an effective method of preventing relapse; in case of hernias of types II-IV and normal length of the esophagus, the use of prosthetic materials to correct the size of the hiatal opening is justified and allows to reduce the frequency of unsatisfactory treatment results.